Fast Radio Bursts Generated by Coherent Curvature Radiation from Compressed Bunches for FRB 20190520B - Xiang-han Cui; Zheng-wu Wang; Cheng-min Zhang; Chen-hui Niu; Di Li; Jian-wei Zhang; De-hua Wang (The Astrophysical Journal, 2023)
The radiation mechanism of fast radio bursts (FRBs) has been extensively studied, but still remains elusive. Coherent radiation has been identified as a crucial component in the FRB mechanism, with charged bunches also playing a significant role under specific circumstances. In the present research, we propose a phenomenological model that draws upon the coherent curvature radiation framework and a magnetized neutron star, taking into account the kinetic energy losses of outflow particles due to inverse Compton scattering (ICS) induced by soft photons within the magnetosphere. By integrating the ICS deceleration mechanism for particles, we hypothesize a potential compression effect on the particle number density within a magnetic tube/family, which could facilitate achieving the necessary size for coherent radiation in the radial direction. This mechanism might potentially enable the dynamic formation of bunches capable of emitting coherent curvature radiation along the curved magnetic field. Moreover, we examine the formation of bunches from an energy perspective. Our discussion suggests that within the given parameter space, the formation of bunches is feasible. Finally, we apply this model to FRB 20190520B, one of the most active repeating FRBs discovered and monitored by FAST. Several observed phenomena are explained, including the basic characteristics, frequency downward drifting, and bright spots within certain dynamic spectral ranges.